In the footsteps of Ibn Battuta: Consumption and identity-making - Mohamad, J. (Penerbit Universiti Pendidikan Sultan Idris, 2013)
In line with growing prosperity, shopping malls mushroomed in most major cities. these malls have concentrated retail activities in private space while simultaneously replacing the public functions of the street. These new retail outlets have given an opportunity for the urban elites to congregate in new spaces of conspicuous consumption. In addition, there is an increasing tendency to construct these new retail spaces as hyperreal spaces. To illustrate, this article takes on the example of Ibn Battuta mall (IBM), Dubai. Dubai is competing with other cities in the Muslim world, such as Kuala Lumpur to be a model for Muslim modernity. In a conscious effort to create a truly Muslim place, IBM has been themed around the travels of renowed 14th century Muslim explorer Ibn Battuta whose journeys had taken him to all the Arab lands and beyond, even as far as to China. The IBM mall, while functioning as a retail outlet, is organized around various Muslim-inspired architectural styles originating from the Mghreb to China, IBM's sis courts signify the most influential places he travelled to-China,India,Egypt,Persia,Tunisia and Andalusia (Muslim Spain). Hyperreal spaces are made to function as symbolic capital in the global competition for recognition. Towards this end, hyperralities are then often sought to convey a new image of place.